Pengembangan Modul Bimbingan Kelompok Teknik Role Playing Untuk Meningkatkan Self Awareness Siswa - Ria Kurniasari; Raudah Zaimah Dalimunthe; Putri Dian Dia Conia (Journal on Education, 2024)
The aim of the research is to develop media in the form of modules with a group guidance approach to role playing techniques to increase the self-awareness of class XI students at SMAN 1 Kramatwatu. The research method used is research and development (R&D) with the ADDIE development model. The data collection technique uses a questionnaire and the data analysis technique uses a Likert scale. The results of the feasibility test obtained an overall result of 90% with a very feasible category with the provisions of the material and media feasibility test obtaining a result of 86%, the language feasibility test of 94% and the practitioner feasibility test of 93% and to strengthen the effectiveness of the services provided the N-Gain percent result was 57.61%, namely quite effective with a score of 0.57 in the medium category. From the results of this management, the module was declared suitable for use by guidance and counseling teachers in providing understanding to students regarding self-awareness.